Peran Guru Mempersiapkan Generasi Tanggguh Melalui Penanaman Sikap Toleransi dalam Pembelajaran Sejarah Berbasis Contextual Teaching and Learning - Siharta Leman Anwar Nababan; Warto Warto; Triana Rejekiningsih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to explain the role of teachers in preparing a tough generation through inculcating an attitude of tolerance in history learning. This research is also important in overcoming problems that occur in society, especially in terms of intolerance. Teachers in their duties not only teach students in building their knowledge, but teachers also have a very important role in shaping and building the character of students, especially the attitude of tolerance in an effort to create a tough generation through history learning. Learning history, which actually has social values, can of course be used by teachers in instilling tolerance in students. It is important to inculcate an attitude of tolerance to create unity and peace in order to reduce the problem of intolerance that often occurs. The method used in this article is through normative research or through literature searches such as books, journals, papers and other sources that are considered to be similar or relevant. The results of the research in this article indicate that the teacher's efforts to instill an attitude of tolerance are by using the Contextual Teaching and Learning method.